Realizing depth measurement and edge detection based on a single metasurface - Yang Siwen; Wei Qunshuo; Zhao Ruizhe; Li Xin; Zhang Xue; Li Yao; Li Junjie; Jing Xiaoli; Li Xiaowei; Wang Yongtian; Huang Lingling (Nanophotonics)
How to simultaneously obtain the depth, edge, and other light information of the scene to accurately perceive the physical world is an important issue for imaging systems. However, such tasks usually require bulky optical components and active illumination methods. Here, we design and experimentally validate a single geometric metasurface that can achieve depth measurement or edge detection under incoherent or coherent light respectively. Double helix point source function is utilized, and three verification experiments are carried out, including double-helix beam calibration, 2D object and 3D object detection, respectively. Additionally, two-dimensional edge detection can also be achieved. This compact imaging system can enable new applications in various fields, from machine vision to microscopy.